Monitoring Korosi Discharge Conveyor F pada Tambang Batubara PT XYZ di Kabupaten Bungo, Provinsi Jambi - Rahmat Fauzi; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2023)
Abstract. The need for coal is increasing every year to make it easier to transport it using a mechanical device in the form of a conveyor that can increase work efficiency in coal mines. Conveyor structures made of carbon steel material are prone to corrosion due to the influence of the surrounding environment, so they can be damaged and reduce the remaining life of the conveyor structure. The research methodology used was measuring the decrease in the thickness of the conveyor structure which was applied using the Smart Sensor Ultrasonic Thickness Gauge TT 130. Measurements were made on a 125 meter long conveyor structure and 32 test points. The environmental conditions of the study area are based on statistics for 2016–2020 with an average rainfall of 200.48 mm/year, an average air temperature of 25.37ºC and a relative humidity of 87.46%. The type of corrosion that occurs in the conveyor structure is uniform corrosion. The corrosion control method applied is the 3 layer system coating method, which uses a primary coating Seaguard 5000, intermediate coating uses Sherglass FF and top coating uses Aliphatic Acrylic Modifield Polyurethane. The corrosion rate ranges from 0.1827–0.3267 mm/year which is included in the good category based on the relative corrosion resistance table of steel. The design life of the conveyor structure is 15 years and the service life is 7.5 years, while the remaining service life from the calculation results ranges from 6.53–8.79 years. because of that there are 5 test points or 15,6% predicted not to reach the design life of 15 years. Abstrak. Kebutuhan batubara setiap tahun semakin meningkat untuk mempermudah setiap pengangkutannya menggunakan alat mekanis berupa conveyor yang dapat meningkatkan efesiensi kerja pada tambang batubara. Struktur conveyor yang terbuat dari material baja karbon rentan mengalami korosi akibat dari pengaruh lingkungan sekitarnya, sehingga dapat mengalami kerusakan dan mengurangi remaining service life struktur conveyor. Metodologi penelitian yang digunakan adalah pengukuran pengurangan ketebalan struktur conveyor yang diaplikasikan menggunakan alat Smart Sensor Ultrasonic Thickness Gauge TT 130. Pengukuran dilakukan pada struktur conveyor sepanjang 125 meter dan 32 test point. Kondisi lingkungan daerah penelitian berdasarkan statistik tahun 2016–2020 dengan curah hujan rata-rata sebesar 200,48 mm/tahun, temperatur udara rata-rata sebesar 25,37ºC dan kelembapan relatif 87,46%. Jenis korosi yang terjadi pada struktur conveyor adalah jenis korosi merata. Metode pengendalian korosi yang diaplikasikan yaitu metode coating sistem 3 layer, dimana menggunakan primer coating Seaguard 5000, intermediate coating menggunakan Sherglass FF dan top coating menggunakan Aliphatic Acrylic Modifield Polyurethane. Corrosien rate berkisar 0,1827–0,3267 mm/tahun yang termasuk kedalam kategori good berdasarkan tabel ketahanan korosi relatif baja. Umur desain struktur conveyor 15 tahun dan umur pakai 7,5 tahun, sedangkan remaining service life dari hasil perhitungan berkisar 6,53–8,79 tahun. Oleh sebab itu terdapat 5 test point atau 15,6% diprediksi tidak dapat mencapai umur desain yaitu 15 tahun.